Neurotrophic factor of the brain as a marker of restoration of motor and cognitive functions in the acute period of cardioembolic and atherothrombotic ischemic stroke - Yaroslava Havlovska; Nataliia Lytvynenko; Oksana Shlykova; Olga Izmailova; Oleksandr Havlovskyi; Anastasiia Shkodina (Bogomolets National Medical University, 2022)
cerebral ischemic stroke is one of the most common diseases leading to psycho-emotional, cognitive and movement disorders. Modern research is aimed at searching for biological markers of brain damage in the diagnosis of strokes, in particular physical, imaging, electrophysiological, histological, genetic and neuronal markers, the determination of which can accelerate differential diagnosis. The purpose of the study was to assess the level of brain-derived neurotrophic factor in the blood, the state of motor and cognitive functions in the acute period of ischemic stroke on days 1 and 14, as well as the possibility of using the level of blood-brain neurotrophic factor as a marker of restoration of the motor and cognitive functions in atherothrombotic and cardioembolic subtypes of ischemic stroke. The study included 34 people diagnosed with acute ischemic stroke. Depending on the results of the clinical examination, the patients were divided into 2 groups: group 1 - patients in whom ischemic stroke occurred due to atherosclerotic lesions of the vessels of the carotid system with the development of occlusion by the mechanism of atherothrombosis (17 people), group 2 - patients in whom ischemic stroke occurred against the background of damage to the vessels of the carotid system with the development of occlusion by the cardioembolic mechanism (17 people). To compare clinical and laboratory parameters, a control group was additionally identified (patients of the neurological department who did not have damage to the central nervous system - 11 people). Examination of patients was performed on 1 and 14 day of the disease. Motor functions were assessed by the degree of daily activity of life, which was determined by the Barthel index, the state of cognitive functions - by the scale of Mini-Mental State Examination Mental State Examination. The Bartel index on the 1st day of the acute period of ischemic stroke was in the range of mild dependence for the cardioembolic subtype and moderate for atherothrombotic. Within 14 days, the studied patients of both groups had the increased index to the level of complete independence in group 1 and mild dependence in group 2. Among the examined patients with ischemic stroke, average values on the MMSE scale were determined at the level of moderate cognitive deficit per day in both subtypes of ischemic stroke. Restoration of cognitive function within 14 days after ischemic stroke occurred only in the second group before mild cognitive impairment. The concentration of neurotrophic factor of the brain on the 1st day of ischemic stroke decreased sharply compared with the control group. The obtained results allow to consider the brain neurotrophic factor as a prognostic objective biomarker of the prognosis of the restoration of motor and cognitive functions and the severity of cardioembolic and atherothrombotic ischemic stroke.